Combination of Transforaminal and Interlaminar Percutaneous Endoscopic Lumbar Diskectomy for Extensive Down-migrated Disk Herniation - Choi, Kyung-Chul; Lee, Jung Hyun; Kim, Jin-Sung; Lee, Dong Chan; Park, Choon Keun (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims The technique and instrumentation of percutaneous endoscopic lumbar diskectomy (PELD) have significantly improved. Thus its indications have been gradually expanding. Down-migrated disk, in particular, is regarded inaccessible by rigid instrumentation due to poor visualization and limited accessibility. We introduce a combination of transforaminal and interlaminar PELD for extensive down-migrated disk herniation at the L4–L5 level.Patients and Methods In the first case, a 48-year-old man had left L5 radicular pain. Magnetic resonance imaging (MRI) showed that L4–L5 disk herniation extended to the L5 lower end-plate level. In the second case, a 39-year-old man presented with right L5 and S1 radiculopathy. MRI showed right huge extensive down-migrated disk herniation from the L4–L5 disk space to the S1 pedicle level. Back pain and leg pain were measured using the visual analog scale (VAS). In the first case, transforaminal PELD with foraminoplasty removed the disk fragment from the L4–L5 disk space to the mid-L5 pedicle level. Interlaminar PELD removed the remaining disk below the mid-L5 pedicle. In the second case, first, contralateral (left) transforaminal PELD at L4–L5 removed disk fragments located at the subannular and subligamentous area as well as the upper part of the down-migrated disk herniation. Second, interlaminar PELD via an ipsilateral (right) L5–S1 interlaminar space removed the remains of the extensively down-migrated disk herniation.Results In the first case, the VAS scores for back and leg pain were improved from 6 and 8 to 2 and 1, respectively. Postoperative MRI showed complete removal of the disk fragment. In the second case, the VAS scores for back and leg pain improved from 7 and 9 to 3 and 1, respectively, after PELD. Postoperative MRI showed complete removal of a huge disk herniation. Both patients were discharged the day after PELD. Follow-up examinations showed no recurrence.Conclusions It is difficult to remove entire disk fragments using only a transforaminal or interlaminar approach for extensive down-migrated disk herniation. Therefore a combination of transforaminal and interlaminar PELD may be effective for extensive down-migrated disk herniation at L4–L5.
Keywords: percutaneous endoscopic lumbar diskectomy; transforaminal; interlaminar; down-migrated disk herniation; foraminoplasty